7.II The Ascidians of Jørgen Brønlund Fjord, North Greenland. - Lützen, Jørgen (Meddelelser om Grønland, 1970)
Six species of ascidians are recorded from J0rgen Dr0nlund Fjord, North Greenland, one of which, Cnemidocarpa squamata n. sp., is new to science. The horizontal and vertical distribution of the ascidians within the area is reviewed.